1997
DOI: 10.12968/ijpn.1997.3.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care for people dying from chronic obstructive airways disease

Abstract: Nursing has demonstrated its ability to respond to the palliative care needs of patients, and their families, with advanced cancer. One of the current challenges to palliative care nursing lies in meeting the needs of patients with a diagnosis other than cancer. This paper reports on how nursing is currently organised and delivered to those individuals dying from chronic obstructive airways disease (COAD). The study findings illustrate a group of people whose quality of life is perceived to be poor, and whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
3
7
0
Order By: Relevance
“…’s (2001) comparative study, for example, found that 39% of end‐of‐life COPD patients had contact with DNs (compared with 50% in patients with malignancy) but it did not go further to discuss the actual interaction. This was similar in studies by Skilbeck et al. (1997) and Elkington et al.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…’s (2001) comparative study, for example, found that 39% of end‐of‐life COPD patients had contact with DNs (compared with 50% in patients with malignancy) but it did not go further to discuss the actual interaction. This was similar in studies by Skilbeck et al. (1997) and Elkington et al.…”
Section: Introductionsupporting
confidence: 91%
“…Edmonds et al's (2001) comparative study, for example, found that 39% of end-of-life COPD patients had contact with DNs (compared with 50% in patients with malignancy) but it did not go further to discuss the actual interaction. This was similar in studies by Skilbeck et al (1997) and Elkington et al (2005). Skilbeck et al's (1998) later study did in fact note that the interaction between DNs was strictly taskbased, but it did not reflect on the broader patient needs.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Further studies have been carried out to identify the palliative care needs of other groups of patients. Skilbeck et al (1997) found that patients with chronic obstructive airways disease stressed the psychosocial elements of care, and described their palliative care needs as symptom control, support in daily activities, emotional support, social support and information. Perhaps the work of Addington‐Hall (1998) summarizes the particular needs of many people dying from non‐malignant causes.…”
Section: Similarities Between Palliative Care Nurses and Mental Healtmentioning
confidence: 99%